Implementation of technology-driven policy for high-technology sectors: A case of Malaysia's commercialisation fund - Dzulkifli Mukhtar; Mohd Hafizie Suhaimi; Muhammad Naqib Mat Yunoh (Intercontinental Management Research Consortium, 2016)
The aim of this exploratory study is to investigate the impact of technology-driven growth strategies on high-technology industrialisation within developing economies. It sheds light on the issue of high technology sectors development in contexts of a developing economy like Malaysia. This study focuses on forms of initiatives that have been developed by the Malaysian government as part of technology-driven growth strategies. These strategies are argued to translate into industrial policies that guide development of the country. This study is not concerned with the highest level of industrial policy (i.e. why governments decide to pursue particular policies). Rather, it focuses on one part of industrial policy that is particularly applicable to the development of high-technology in Malaysia.